2021
DOI: 10.1186/s12934-021-01567-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of ectoine and hydroxyectoine as high-value chemicals

Abstract: Ectoine and hydroxyectoine as typical representatives of compatible solutes are not only essential for extremophiles to survive in extreme environments, but also widely used in cosmetic and medical industries. Ectoine was traditionally produced by Halomonas elongata through a “bacterial milking” process, of which the marked feature is using a high-salt medium to stimulate ectoine biosynthesis and then excreting ectoine into a low-salt medium by osmotic shock. The optimal hydroxyectoine production was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 78 publications
3
46
0
Order By: Relevance
“…The cyclic amino acid ectoine (1,4,5,6-tetrahydro-2-methyl-4-pyrimidinecarboxylic acid) is a representative compatible solute that is wide-spread among halophilic and halotolerant eubacteria ( Liu et al, 2021 ). It not only functions as osmoprotectant, biofunctional stabilizer, skin protector, and potential drugs for diseases but also is widely used in cosmetic and medical industries ( Liu et al, 2021 ).…”
Section: Extending and Intercepting Biosynthetic Routes To Produce Ni...mentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic amino acid ectoine (1,4,5,6-tetrahydro-2-methyl-4-pyrimidinecarboxylic acid) is a representative compatible solute that is wide-spread among halophilic and halotolerant eubacteria ( Liu et al, 2021 ). It not only functions as osmoprotectant, biofunctional stabilizer, skin protector, and potential drugs for diseases but also is widely used in cosmetic and medical industries ( Liu et al, 2021 ).…”
Section: Extending and Intercepting Biosynthetic Routes To Produce Ni...mentioning
confidence: 99%
“…The cyclic amino acid ectoine (1,4,5,6-tetrahydro-2-methyl-4-pyrimidinecarboxylic acid) is a representative compatible solute that is wide-spread among halophilic and halotolerant eubacteria ( Liu et al, 2021 ). It not only functions as osmoprotectant, biofunctional stabilizer, skin protector, and potential drugs for diseases but also is widely used in cosmetic and medical industries ( Liu et al, 2021 ). Since ectoine production in the halophilic microbes through ‘bacterial milking’ process causes corrosive damage to devices, its production process under low salt conditions is crucial for economical production ( Wolf et al, 2021 ).…”
Section: Extending and Intercepting Biosynthetic Routes To Produce Ni...mentioning
confidence: 99%
“…Ectoine and hydroxyectoine are of particular interest, because they have particularly powerful effects in stabilizing cells and biomolecules [15,16]. They have applications in stabilizing cells against stress [17,18] and are used widely in skin care [19], with sales estimated at 15000 tonnes per annum [20], generating a market of tens of millions of US dollars per year [21]. They have also been proposed to be useful for treatment of eye irritation [22], allergic rhinitis [23] and Alzheimer's disease [24].…”
Section: Introductionmentioning
confidence: 99%
“…The heterologous expression of the gene cluster ectABC from halophiles in nonnatural ectoine producers, such as Escherichia coli and Corynebacterium glutamicum (Pérez-García et al, 2017), can facilitate the fermentative production of ectoine in the absence of osmotic stress, and ectoine titers as high as 25.1 g/L in E. coli (Ning et al, 2016) and 65 g/L in C. glutamicum (Gießelmann et al, 2019) have been reported. However, the metabolic engineering for hydroxyectoine production faces more challenges, and comparatively fewer studies have examined hydroxyectoine production (Liu et al, 2021). The conversion of ectoine to hydroxyectoine is catalyzed by ectoine hydroxylase, which is encoded by ectD, and requires the co-substrate α-ketoglutarate and other factors including iron (II) and molecular oxygen (Bursy et al, 2007;Chen et al, 2019).…”
mentioning
confidence: 99%
“…To date, the highest reported heterologous fermentative production of hydroxyectoine in E. coli was only 1.6 g/L with glycerol as carbon source; however, 4% ectoine still accumulated, and a salinity of 0.5% NaCl was required for enhancement of hydroxyectoine synthesis (Bethlehem & Moritz, 2020). In sum, the development of a cost-effective process in the absence of osmotic stress that can support sole hydroxyectoine production (i.e., without producing ectoine) remains a major challenge (Liu et al, 2021).…”
mentioning
confidence: 99%